close
    Solving linear equations substitution

    x+y=3    3x-y=1

    0  Views: 365 Answers: 1 Posted: 6 years ago

    1 Answer

    <font face="Arial, 'liberation sans', sans-serif">
    </font>


    <font face="Arial, 'liberation sans', sans-serif">x+y=3, 3x-y=1
    move x the the other side of the first equation: y=3-x
    then substitude y in the second equation with 3-x --> 3x-(3-x)=1 ---> 3x-3+x=1 ---> 4x=4 ---> x=1
    </font>



    Top contributors in Mathematics category

     
    ROMOS
    Answers: 313 / Questions: 0
    Karma: 13510
     
    Colleen
    Answers: 367 / Questions: 0
    Karma: 6890
     
    country bumpkin
    Answers: 97 / Questions: 0
    Karma: 6225
     
    Bob/PKB
    Answers: 220 / Questions: 2
    Karma: 5030
    > Top contributors chart

    Unanswered Questions

    442242
    questions
    711247
    answers
    520314
    users